Peran Guru Pendidikan Agama Islam dalam Membentuk Sikap Toleransi Beragama di Era Digital Siswa Kelas II SD Negeri 007 Bontang Utara Tahun Pelajaran 2023/2024 - Wati, Rima; Ihsan, Muh.; Munir, Misbahul (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This research discusses the role of Islamic Religious Education teachers in forming attitudes of religious tolerance in the digital era of class II students at SD Negeri 007 North Bontang for the 2023/2024 academic year. This research aims to determine the role of Islamic Religious Education teachers in forming students' attitudes of religious tolerance as well as forms of student tolerance in the digital era by conducting observations, interviews and documentation to collect data. The research results show the important role of Islamic Religious Education teachers in forming attitudes of religious tolerance through conveying messages of tolerance, mentoring in religious activities, and providing role models. Based on the research that has been conducted, it can be concluded that the role of Islamic Religious Education teachers in forming an attitude of religious tolerance is to provide understanding regarding mutual respect and appreciation for both those of the same religion and those of different religions. So that a good attitude of religious tolerance is formed in students, such as mutual respect and respect for fellow friends, working together, playing, helping students who have difficulty viewing religion, eating together after religious activities and being obedient and obedient to all teachers, both Muslims and non-Muslims.